Prototype motion control system for CSNS very small angle neutron scattering instrument - HE Yongcheng; XIAO Songwen; WANG Guangyuan; JIN Dapeng; ZHANG Yuliang; WU Xuan; XUE Kangjia; ZHU Peng; WANG Lin; ZUO Taisen; CHENG He (He jishu, 2022)
BackgroundVery small angle neutron scattering (VSANS) instrument is a powerful tool for structure calibration.PurposeThis study aims to ensure the repeat positioning accuracy is better than ±2 μm for the moving parts of VSANS instrument at China spallation neutron source (CSNS).MethodsA prototype motion control system based on experimental physics and industrial control system (EPICS) software architecture was designed. The stepper motor was used to drive the movement of the displacement platform, the absolute optical encoder was applied to feedback of the real-time position of the displacement platform, and the Beckhoff embedded controller was employed to implement the full closed loop control of the position of the displacement platform.Results & ConclusionsThe test results show that the repeat positioning accuracy of this prototype motion control system is better than ±2 μm with high stability and high reliability, satisfying the needs of the VSANS instrument at CSNS.